Empirical evidence on the success of R&D co-operation: Happy together? - Birgit Aschhoff; Tobias Schmidt (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
In this paper we analyse the effect of R&D co-operation on firms? innovation performance. We investigate the effect of past co-operation on current sales of innovative products, distinguishing between products new to the firm and new to the market, and on cost reductions due to innovative processes. Particular attention is paid to the impact of different co-operation partners. The analysis rests on firm-level data from two consecutive waves of the annual German innovation survey. We find that innovative firms that cooperate have a higher share of turnover with market novelties and a higher share of cost reduction due to process innovations than non-cooperating firms. In particular, R&D cooperation with research institutes has a positive influence on a firm's economic success with market novelties, while R&D co-operation with competitors leads to an increase in the cost reduction attributable to innovative processes.
Keywords: C24; O31; L25; 330; R&D Co-operation; Innovation Success; Germany; Applied Econometrics